Tourism Retribution as a Source of Local Revenue: Insights from Bone Bolango Regency - Monantun, Widy Pratiwi (Journal of Accounting Inquiry, 2024)
Purpose: This study aims to examine the contribution and growth rate of tourism retribution (including regional wealth retribution, special parking fees at tourist sites, and recreational area retribution) to locally-generated revenue (LGR) in Bone Bolango Regency, Gorontalo Province, Indonesia. The study also seeks to identify the challenges and opportunities in optimizing tourism retribution as a revenue source. Methodology: A quantitative research approach was applied. Data were collected from the Tourism and Creative Economy Office and the Central Bureau of Statistics of Bone Bolango Regency. The analysis involved calculating contribution and growth rate to assess the performance of tourism retribution.Findings: The research findings show that the contribution of tourism retribution to the Locally-generated revenue of Bone Bolango Regency from 2017 to 2021 was relatively low, ranging from 0.006% to 0.61%, with the highest contribution in 2019 at Rp465,573,000.00 (0.61%) and the lowest in 2017 at 0.006%. Additionally, tourism retribution receipts experienced significant fluctuations, with the highest growth rate of 391.58% in 2018, a sharp decline of -77.70% in 2020 due to the impact of the COVID-19 pandemic, and recovery reaching Rp328,340,005 with a growth rate of 216.30% in 2021. Novelty: This study offers a detailed analysis of tourism retribution as a revenue source. The findings emphasize the need to improve collection strategies to boost LGR, providing valuable insights for policymaking and future research aimed at optimizing local revenue generation.